(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Background: Klebsiella pneumoniae possesses virulence genes (fimH, mrkD, wabG, wcaA, magA) that contribute to its high pathogenicity, ability to cause infections in the community and hospitals, as well as its antibiotic resistance and difficulty in treatment. Objective: This study investigated the prevalence of some virulence genes in Klebsiella pneumoniae in local clinical isolates in Baqubah, Iraq and identified local strains and their relationship to each other using ERCI-PCR. Methodology: A total of 285 clinical samples (urine, wound swabs, sputum, vaginal swabs, burn swabs, and blood) were collected from patients attending health centers and outpatient clinics in Baqubah, Iraq, between March to May 2024, Samples were transported to the laboratory within 2 hours and processed according to standard microbiological procedures. Ethical approval was obtained from the Institutional Review Committee of the University of Diyala. PCR was used to detect virulence genes. ERIC-PCR was used to identify local isolates’ molecular profiling. Genetic relationship was determined by Past Software. Results: Twenty-four (8.42%) Klebsiella pneumoniae isolates were identified by morphological, microscopic, and biochemical characteristics. The frequency of fimH, mrkD, wabG, wcaA and magA genes was 58.3%, 91.6%, 37.5%, 4.1% and 0.0% respectively. Molecular typing of 24 Klebsiella pneumoniae isolates using ERIC-PCR revealed 11 different Geno patterns, including four clons and seven single isolates. Conclusions: In conclusion, Klebsiella pneumoniae isolates carrying high levels of the fimH and mrkD genes, which contribute to biofilms production, increase their resistance to antibiotics. ERIC-PCR showing genetic relationships between local isolates and helps in epidemiological surveillance to identify the spread of strains. Bangladesh Journal of Infectious Diseases, June 2025;12(1):116-124